Taxation in Nepal: Structure, Issues and Reforms - Dahal, Madan Kumar (Economic Journal of Nepal, 2011)
In developing economies resource gap is critical and widening resulting to huge fiscal and budgetary deficits. The growing resource gap is frequently of by mobilizing internal and external borrowings and consequently shifting the burden of debt to posterity. Therefore, revenue mobilization is challenging proposition in an economy like Nepal where a majority of the people live in abject poverty and the people engaged in economic activities have extremely limited taxable capacity. In addition, legal base of taxation is compressed with unlimited tax shelters and tax administration lacks innovative mechanism to identify new taxpayers and bring them into taxnet. The tar of or tax burden ratio is estimated to be 15.7% of GDP in FY 2008/09. In Nepal’s tax structure revenues are buoyant but inadequate to supplement development activities. Interestingly. there was no adverse impact of conflict on internal revenues and. subsequently. ODA to Nepal have increased over the years. The tax system .suffers from structural constraints with tremendous administrative and procedural complexities envisaged in the existing Income Tax Act, which lacks simplicity and transparency. The major problems of taxation in Nepal include: (1) marginally high tar rates (2) limited tar base (3) low lax elasticity (4) poor voluntary compliance (4) leakages in tax collection (5) rigid Income Tax Art, 20(K) (6) inefficient, indifferent and corrupt tax administration, and (7) no consolidated record of property (land and building) with the Internal Revenue Department. The tax system in Nepal calls for a periodic reforms to ensure growth, equity and stability. The studies and reports on taxation exhibit that several reforms have had been undertaken by the government in the past to simplify and modernize the tax system These reforms were confined to improving tax structure by designing appropriate policy instruments. The reforms in taxation in Nepal consist of three types: (1) reforms in tax laws and regulations (2) reforms in environment, and (3) reforms in tar administration. Key words: Taxation; Economics; Poor Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics T.U., Kirtipur Vol. 32, No. 1 January-March 2009, Issue No. 125 Page: 1-13 Uploaded date: 5 July 2011